Energy efficient wireless sensor network for long term continuous acquisition and monitoring of physiological parameters : doctoral thesis - Celić, Luka (L. Celić ; Fakultet elektrotehnike i računarstva, 2020)
Research in this thesis was to apply best practices in energy efficiency and wireless communication to lower adoption barriers of wearable devices, increase perceived usefulness, implement non-invasive devices for long-term continuous acquisition and monitoring of physiological parameters and extended cycles between device charging. As wireless communication accounts for largest part of the sensor node consumption, it is crucial to use energy efficient wireless sensor networks. An overview is given of technologies used in wireless sensors network for healthcare. The absence of the comprehensive energy efficient wireless sensor network solution capable to guaranty consistent low power consumption across full bandwidth range, consistent bandwidth regardless of number of connected nodes and automatically adaptable bandwidth and latency based on changing requirements when device is in use are discussed. The research resulted in defining, development and validation of two architectures of energy efficient wireless sensors network in healthcare; i) architecture based on novel wireless and packet distribution protocols, ii) architecture designed to provide interoperability and seamless connectivity exploiting existing standards, technologies and best practices. Successful validation and implementation of custom developed platform and protocols was made and showed fulfilling of the research and design goals. Keywords: WSN, energy efficiency, low power consumption, seamless connectivity